The East African community and common market - Detter Delupis, Ingrid (London : Longman, 1970)
The book includes a detailed examination of the historical background, the structure and function of the East African Community, a full account of its common market, of the Agreement between that Common Market and the European Economic Community and a comparison between that and the Association agreement concluded between the E.E.C. and other African countries.
Bibliography: p. 180.
osc 03/10/2018
Loans
Keywords: Economic cooperation; Africa, East